The Socio-Economic Impacts of Ebola in Liberia : Results from a High Frequency Cell Phone Survey, Round 5 - Himelein, Kristen; Kastelic, Jonathan G. (World Bank, Washington, DC, 2015)
Since Liberia’s Ebola virus disease (EVD) epidemic began in March 2014, nearly 10,000 persons have contracted the virus and more than 4,000 have died. The economic impact of Ebola survey is a high frequency cell phone survey designed to monitor the socio-economic impacts of the EVD crisis in Liberia. The survey has been conducted in five rounds from October 2014 to March 2015. The sample is based on the nationally representative household income and expenditure survey (HIES) implemented from February to August 2014 by the Liberia institute of statistics and geo-information services (LISGIS). The report presents an update of the epidemiological situation in Liberia and associated response efforts at the time of the fifth round of data collection (March 12-18, 2015). It gives an updates on the employment, prices, food security, coping strategies, health, and education indicators surveyed.